Pseudomonas nunensis sp. nov. isolated from a suppressive potato field in Greenland. Issue 2 (7th February 2023) - Ntana, Fani; Hennessy, Rosanna C.; Zervas, Athanasios; Stougaard, Peter
Abstract : The bacterial strain In5 T was previously isolated from a suppressive potato field in southern Greenland and has been characterized and described as Pseudomonas fluorescens . However, the results of new polyphasic analyses coupled with those of phenotypic, phylogenetic and genomic analyses reported here demonstrate that the affiliation to the species P. fluorescens was incorrect. The strain is Gram-stain-negative, rod-shaped, aerobic and displays growth at 4–28 °C (optimum temperature 20–25 °C) and at pH 5–9 (optimum pH 6–7). Major fatty acids were C16 : 0 (38.2 %), a summed feature consisting of C16 : 1 ω6 c and/or C16 : 1 ω7 c ) (20.7 %), C17 : 0 cyclo ω7 c (14.3 %) and a summed feature consisting of C18 : 1 ω6 c and/or C18 : 1 ω7 c (11.7 %). The respiratory quinones were determined to be Q9 (95.5 %) and Q8 (4.5 %) and major polar lipids were phosphatidylethanolamine, phosphatidylglycerol and diphosphatidylglycerol. The DNA G+C content was determined to be 59.4 mol%. The results of phylogenetic analysis based on the 16S rRNA gene and multi-locus sequence analysis (MLSA; concatenated 16S rRNA, gyrB, rpoB and rpoD sequences) indicated that In5 T was affiliated with the Pseudomonas mandelii subgroup within the genus Pseudomonas . Comparison of the genome sequence of In5 T and those of related type strains of species of the genus Pseudomonas revealed an average nucleotide identity (ANI) of 87.7 % or less and digital DNA–DNA hybridization (dDDH) of less than 34.5 % relatedness, respectively. Two more strains, In614 and In655, isolated from the same suppressive soil were included in the genome analysis. The ANI and dDDH of In614 and In655 compared with In5 T were ANI: 99.9 and 97.6 and dDDH (GGDC) 99.9 and 79.4, respectively, indicating that In5 T, In614 and In655 are representatives of the same species. The results of the phenotypic, phylogenetic and genomic analyses support the hypothesis that strain In5 T represents a novel species of the genus Pseudomonas, for which the name Pseudomonas nunensis sp. nov. is proposed. The type strain is In5 T (=LMG 32653 T =NCIMB 15428 T ).